2004
DOI: 10.1177/10598405040200040801
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses’ Perceptions of Empowerment and Autonomy

Abstract: The purpose of this study was to explore Kanter's Theory of Structural Power in Organizations, using school nurses and to answer the research question of whether there is a relationship between empowerment and autonomy in school nurses. This study found a positive relationship between the nurses' perceptions of empowerment and autonomy. The school nurses surveyed perceived themselves to have a high degree of autonomy and a moderate degree of empowerment, and they reported that their access to informal power st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The low sense of accomplishment and powerlessness expressed by the study participants is supported by other studies (DeSisto & DeSisto, 2004; Simmons, 2002). According to the U.S.…”
Section: Discussionsupporting
confidence: 85%
“…The low sense of accomplishment and powerlessness expressed by the study participants is supported by other studies (DeSisto & DeSisto, 2004; Simmons, 2002). According to the U.S.…”
Section: Discussionsupporting
confidence: 85%
“…DeSisto and DeSisto (2004) conducted a study to determine the relationship between empowerment and autonomy in 82 school nurses. Formal power structures, which consist of access to opportunity, information, support, and resources, as well as informal power structures, including size and variety of alliances with superiors, peers, and subordinates, were studied in relation to school nurses’ autonomy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature, as well as field work by this researcher, suggests that school nurses are experiencing increasing levels of frustration in relation to practice issues over which they have little influence or control. Studies of acute care nurses demonstrated that empowerment leads to increased productivity and work effectiveness (Kuokkanen & Leino-Kilpi, 2001), yet school nurses have consistently recognized and acknowledged a sense of powerlessness as well as a lack of participation in decision making regarding pertinent practice matters (DeSisto & DeSisto, 2004; Felton & Keil, 1998; Simmons, 2002). According to Moss (1995), feelings of powerlessness are related to job dissatisfaction and low levels of professional commitment, both of which can inhibit the delivery of quality nursing care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two characteristics, autonomy and empowerment, are known to be facilitators of the use of EBP in other nurse populations. Available studies on school nurse characteristics related to job satisfaction have indicated that school nurses report a high degree of both autonomy and empowerment (Desisto & Desisto, 2004; Foley and colleagues, 2004; Simmons, 2002). In addition, many school nurses are in a unique position of deciding on best practice methods without the structure of a supervisory hierarchy.…”
Section: Evidence-based Practicementioning
confidence: 99%